Drought hardiness of sea buckthorn (Hippophae rhamnoides L.) varieties in conditions of Orel region. - З. Є. Ожерельєва; Н. І. Богомолова (Plant Varieties Studying and Protection)
The estimation of drought hardiness of sea buckthorn varieties of different environmental and geographical origin was made in the field and laboratory conditions. In late August the drought hardiness was estimated according to leaf injures and abscission in the field conditions. In the laboratory conditions were determined the main characteristics of water regime: tissue water saturation, water deficit, leaf water retaining ability. As a consequence, the studied varieties were divided into groups with different drought hardiness degree.